2019
DOI: 10.1155/2019/5120275
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Protects Intervertebral Disc from Degeneration by Improving Cell Survival and Function via Activation of the ERK1/2 Signaling Pathway

Abstract: Melatonin, a neuroendocrine hormone secreted by the pineal body, has a positive effect on intervertebral disc degeneration. The present study is aimed at investigating the biological role of melatonin in intervertebral disc degeneration and its underlying mechanism. A human nucleus pulposus cell (NPC) line was exposed to melatonin at different concentrations. Cell proliferation was measured by CCK-8 assay. Cell cycle and apoptosis were analyzed by flow cytometry. Western blot was performed to measure the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 56 publications
(49 reference statements)
1
26
0
Order By: Relevance
“…Our results indicated that melatonin significantly increased the level of p-ERK1/2 and the inhibition of the ERK1/2 signaling pathway reversed melatonin-induced Sertoli cell proliferation and down-regulated the expression of CCND1, PCNA, and INHA. Recently study has shown that melatonin promotes viability in human nucleus pulposus cells (NPC) and activates the ERK signaling pathway, but inhibition of the ERK signaling pathway reverses the effects of melatonin on NPC [33]. Melatonin can also promote osteoblast differentiation through the ERK signaling pathway [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that melatonin significantly increased the level of p-ERK1/2 and the inhibition of the ERK1/2 signaling pathway reversed melatonin-induced Sertoli cell proliferation and down-regulated the expression of CCND1, PCNA, and INHA. Recently study has shown that melatonin promotes viability in human nucleus pulposus cells (NPC) and activates the ERK signaling pathway, but inhibition of the ERK signaling pathway reverses the effects of melatonin on NPC [33]. Melatonin can also promote osteoblast differentiation through the ERK signaling pathway [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the protective effect of melatonin in IDD was also reported. Ge et al ( 14 ) revealed that the melatonin was able to upregulate the expression of collagen-II and aggrecan via elevating the activity of the ERK signaling pathway in a rabbit model of IDD. Melatonin also ameliorated IDD via mitophagy induction and apoptosis inhibition ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is an endogenous molecule released from the pineal gland that has a role in the regulation of the circadian rhythm and anti-oxidative stress and has an anti-inflammatory effect ( 14 , 15 ). Recent studies have reported that melatonin may protect IVDs from degeneration by improving cell survival and mitophagy induction ( 14 , 16 ). In addition, melatonin has been reported to exert a potential anti-angiogenic effect ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin suppressed the TLR2/MyD88/p-ERK pathway to reduce IL-2, IL-6, IL-10, IL-17, IFN-γ, and tumor necrosis factor (TFN)-α production, thus subsiding inflammation in Helicobacter pylori-infected mice (87). These effects were mediated by melatonin membrane receptors, MT1 and MT2, as anti-inflammatory effects were reduced by blocking these receptors (88,89). Melatonin blocks the secondary inflammatory cytokine storm caused by damage-associated molecular patterns (DAMPs) of mitochondrial origin.…”
Section: Anti-inflammatory Effects Of Melatoninmentioning
confidence: 99%
“…During inflammation, but not during normal conditions, melatonin is able to downregulate TLR2, TLR4, and TLR9 expression, or inhibit their downstream pathways (153) Luo et al (153) reported that melatonin suppresses the TLR2/MyD88/p-ERK pathway to reduce IL-2, IL-6, IL-10, IL-17, IFN-γ, and TFN-α production, thus subsiding inflammation in H. pyloriinfected mice. Similarly, melatonin reduced the innate immune response by inhibiting the TLR4/ MAPK/NF-κB pathway through its membrane receptors MT1 and MT2, since its antiinflammatory effects were reduced by blocking these receptors (88,89). Through inhibition of the ERK1/2 and AKT pathways, melatonin suppresses TLR9-mediated innate immune responses without involving receptors MT1 and MT2 (154) .…”
Section: Impact Of Melatonin On Innate and Adaptive Immune Responsesmentioning
confidence: 99%